Induced Effects of Nano-Patterned Substrates on the Electrical and Photo-Electrical Properties of PTB7-Th:ICBA (1:1, wt.%) Bulk-Heterojunction Solar Cells - Tudor Suteu; Vlad-Andrei Antohe; Stefan Antohe; Ionel Stavarache; Maria Cristina Balasin; Gabriel Socol; Marcela Socol; Oana Rasoga; Sorina Iftimie (Surfaces)
In this study, we detailed the fabrication and characterization of photovoltaic structures based on PTB7:ICBA (1:1, wt.%) bulk-heterojunction on optical glass substrates by spin-coating. Some samples were deposited on a flat substrate, and others were placed on a patterned substrate obtained by nano-imprinting lithography; the induced effects were analyzed. We demonstrated that using a patterned substrate enhanced the maximum output power, primarily because the short-circuit current density increased. This can be considered a direct consequence of reduced optical reflection and improved optical absorption. The topological parameters evaluated by atomic force microscopy, namely, the root mean square, Skewness, and Kurtosis, had small values of around 2 nm and 1 nm, respectively. This proves that the mixture of a conductive polymer and a fullerene derivative creates a thin film network with a high flatness degree. The samples discussed in this paper were fabricated and characterized in air; we can admit that the results are encouraging, but further optimization is needed.